THE EFFECTIVENESS OF THE INSTRUCTION OF THE MINISTER OF INTERNATIONAL AFFAIRS NUMBER 15 YEAR 2021 CONCERNING IMPLEMENTATION OF LIMITATIONS ON CORONA VIRUS DISEASE EMERGENCY COMMUNITY ACTIVITIES 2019 IN JAVA AND BALI - Soesanto, Abimanyu Iqbal; Fil'laili, Satria (Progressive Law Review, 2021)
This paper will discuss the post-implementation of the Instruction of the Minister of Home Affairs Number on the PPKM policy, which regulates operational restrictions. What is discussed is the position of these regulations in the Indonesian legal system and considerations in human rights values. This paper aims: to provide an understanding to the public that the importance of paying attention to the legal position of a regulation issued by a government agency is an effort so that the public is not blind to the law and to know about the effectiveness of the regulation. The primary data of this paper is the instruction of the Minister of Home Affairs Number 15 of 2020 regarding PPKM, While the secondary data legal materials in this study were obtained from library materials related to the problem. The position of the Minister of Home Affairs Instruction No. 15 of 2021 regarding PPKM has strong legal force even though the Ministerial Instruction is not part of the Hierarchy of Laws Then Regarding PPKM policies carried out by the government in accordance with rights values Human rights are universal, visibility, interdependence, and inalienable. In the context of the implementation of the fulfillment of the rights to freedom, the right to move, the right to work, the right to social security must be based on the principles of universality, equality and non-discrimination. Other than that,